THE IMPACT OF MOBILE APPLICATIONS AND PODCASTS ON DEVELOPING LISTENING COMPREHENSION STRATEGIES IN EFL CLASSROOMS - Atamuradova Jasmina Jahongirovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation: This paper investigates the effectiveness of contemporary digital resources—specifically, mobile apps, podcasts, and interactive platforms—in boosting the listening comprehension abilities of English as a Foreign Language (EFL) students. In the age of Mobile Language Learning (MLL), traditional audio resources are gradually being replaced with high-quality digital materials. The study looks at how services like BBC Learning English, British Council Podcasts, and gamified apps like Duolingo assist both "top-down" and "bottom-up" methods to listening. This study demonstrates that digital technologies not only provide actual language input but also improve learner autonomy and motivation through a qualitative review of known pedagogical frameworks and student interaction patterns. The findings show that introducing interactive platforms into the curriculum allows for personalized learning speeds and quick feedback, which reduces "listening anxiety" and improves long-term retention of material.